Live rubella virus vaccine long‐term persistence as an antigenic trigger of cutaneous granulomas in patients with primary immunodeficiency. (5th March 2014) - Bodemer, C.; Sauvage, V.; Mahlaoui, N.; Cheval, J.; Couderc, T.; Leclerc‐Mercier, S.; Debré, M.; Pellier, I.; Gagnieur, L.; Fraitag, S.; Fischer, A.; Blanche, S.; et al.
Abstract Granulomas may develop as a response to a local antigenic trigger, leading to the activation of macrophages and T‐lymphocytes. Primary immunodeficiency (PID) is associated with the development of extensive cutaneous granulomas, whose aetiology remains unknown. We performed high‐throughput sequencing of the transcriptome of cutaneous granuloma lesions on two consecutive index cases, and RT‐PCR in a third consecutive patient. The RA27/3 vaccine strain of rubella virus—the core component of a universally used paediatric vaccine—was present in the cutaneous granuloma of these three consecutive PID patients. Controls included the healthy skin of two patients, non‐granulomatous cutaneous lesions of patients with immunodeficiency, and skin biopsy samples of healthy individuals, and were negative. Expression of viral antigens was confirmed by immunofluorescence. Persistence of the rubella vaccine virus was also demonstrated in granuloma lesions sampled 4–5 years earlier. The persistence of the rubella virus vaccine strain in all three consecutive cutaneous granuloma patients with PID strongly suggests a causal relationship between rubella virus and granuloma in this setting.